Endovascular EEG device prospective multicenter single-arm clinical trial to confirm efficacy and safety performance on patients with Intractable Epilepsy: The EPSILON IE trial protocol - Yuji Matsumaru; Ayataka Fujimoto; Yosuke Masuda; Hisayuki Hosoo; Kota Araki; Aiki Marushima; Kensuke Kawai; Hiroki Ishida; Koichi Hashimoto; Ryota Ishii; Bryan J. Mathis; Eiichi Ishikawa (PLoS ONE, 2025)
Introduction Epilepsy affects approximately 70 million people globally, with around 20−30% of these individuals experiencing drug-resistant epilepsy in which seizures remain uncontrolled despite prolonged treatment with anti-seizure medications (ASMs). Such refractory epilepsy significantly impairs quality of life, often necessitating surgical resection of the epileptic focus when ASMs fail. Accurate localization of the epileptic focus is crucial for successful surgery and typically requires invasive intracranial monitoring through subdural electrodes (SDE) or stereotactic electroencephalography (SEEG). Despite their effectiveness, the invasiveness of these methods poses significant risks. In response to these challenges, the EP-01 device has been developed to measure intracranial electroencephalogram (EEG) via the cerebral veins, offering a less invasive alternative. The Endovascular EEG Device Prospective Multicenter Single-arm clinical trial to confirm efficacy and safety performance on patients with Intractable Epilepsy (EPSILON IE) trial aims to evaluate the efficacy and safety of EP-01 in diagnosing the lateralization of epileptic foci in patients with focal epilepsy. The hypothesis is that EP-01, when equipped with multiple endovascular EEG electrodes, can accurately diagnose lateralization, reducing the need for more invasive procedures like SDE and SEEG. Methods and analysis This multicenter, prospective, single-arm validation clinical trial is set to take place from March 2024 to August 2025, with follow-up extending to August 2026. The study will enroll 37 patients with refractory focal epilepsy across several Japanese medical institutions. Eligibility criteria include age 15–70 years and a vascular anatomy that allows the EP-01 to be guided into cerebral veins close to the epileptic focus. The EP-01 device will be inserted via the jugular veins, with electrodes positioned in target cerebral veins to record intracranial EEG data. The primary endpoint is the percentage agreement in lateralization diagnosis between EP-01 and conventional intracranial electrodes. Secondary endpoints include the diagnostic performance of EP-01, safety assessments, and seizure outcomes one year after resection surgery. Participants will undergo a screening period of 30 days, followed by the clinical trial period of up to two weeks, during which EP-01 will be inserted and monitored. A post-observation period of one week will follow device removal to assess potential adverse events. Data collection will involve EEG recordings, imaging studies, and safety evaluations, with results analyzed to determine the efficacy and safety of the device compared to traditional methods. This trial aims to provide critical data on the potential for EP-01 to serve as a less-invasive, effective alternative for diagnosing epileptic focus lateralization, potentially reducing the need for traditional invasive monitoring methods.